2023
DOI: 10.1002/ese3.1596
|View full text |Cite
|
Sign up to set email alerts
|

Operation optimization of regional integrated energy systems

Wentao Tang,
Bozhao Wang,
Fulin Wang
et al.

Abstract: To study the role of energy system demand‐side regulation capacity on carbon emission reduction, we proposed a regional integrated energy system (RIES) optimal dispatch model considering carbon trading cost and dynamic demand response (DR). First, based on the framework of the RIES, the impact of DR of transferable load, reducible load, and substitutable load demand on system operation, considering the response characteristics of electrical and thermal load, was analyzed. Second, the carbon quota of the system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Ni, Linna et al [15] designed an integrated IDR scheme, which induced the rational utilization of multiple energy sources and the efficient consumption of renewable energy. Tang, Wentao et al [16] analyzed the impacts of DR of transferable loads, curtailable loads, and substitutable load demands on system operations based on the optimal dispatch model of the regional integrated energy system (RIES), and the results showed that the application of demand DR can improve the energy efficiency of the system. The IDR in Yang, Haizhu et al [17]'s study builds a demand response optimal dispatch model by describing the response of price and substitution response, and the results show that it can satisfy the system supply-demand balance, and at the same time, it can inhibit the stochastic fluctuation of renewable energy and load and improve the stability.…”
Section: Introductorymentioning
confidence: 99%
“…Ni, Linna et al [15] designed an integrated IDR scheme, which induced the rational utilization of multiple energy sources and the efficient consumption of renewable energy. Tang, Wentao et al [16] analyzed the impacts of DR of transferable loads, curtailable loads, and substitutable load demands on system operations based on the optimal dispatch model of the regional integrated energy system (RIES), and the results showed that the application of demand DR can improve the energy efficiency of the system. The IDR in Yang, Haizhu et al [17]'s study builds a demand response optimal dispatch model by describing the response of price and substitution response, and the results show that it can satisfy the system supply-demand balance, and at the same time, it can inhibit the stochastic fluctuation of renewable energy and load and improve the stability.…”
Section: Introductorymentioning
confidence: 99%